Growth kinetics of hardened layers produced during nitriding in ammonia gas environments - Mridha, Shahjahan (2006)
In gas nitriding the thickness of the case depth is reported to increase parabolically with processing time and ammonia content in the NH3/H2 gas mixture which consequently increases the thickness of undesirable surface iron-nitride (white layer). In this investigation two commercial grade low alloy steels were nitrided in gas atmospheres containing 10 to 80% ammonia at 4700, 5200 and 5700C for 6 to 96 h. A metallographic technique was used to reveal different zones of the nitrided surface and the thickness of the diffusion zone was recorded using microscope. The growth kinetics of the diffusion layer of these two steels were analyzed and compared with that of 3% chromium (En40B) steel from literature. The results of the investigation conclusively suggest that the growth rate of the nitrided layer for both steels reached to a maximum with the increase of ammonia content in the gas mixture up to an optimum level where the thickness of the white layer is a minimum. However, the growth rates of the nitrided case are different for different steels.